Food Choice Practices among Underweight and Normal-weight Children under Five Years of Age in West Java, Indonesia - Prasodjo, N.W.; Pandjaitan, N.K.; Kinseng, R.; Khomsan, A. (Pakistan Journal of Nutrition, 2017)
Background and Objective: The nutritional status of underweight children under five years of age (Toddlers) remains a serious problem in Indonesia. Previous studies have shown that children’s nutritional status and health are affected by the social practices related to their food choices. The aim of this study was to identify (1) The types of routine social practices involved in toddlers’ food choices, (2) The effects of these practices on food consumption and nutritional status and (3) The social structures including rules and resources that may be associated with these practices. Methodology: This survey was conducted in rural communities in the highlands and lowlands of West Java Province, Indonesia and included 200 mothers as respondents. The correlations and differences between the variables were determined using t-tests and Spearman’s rank, Pearson and Mann-Whitney tests. Results: The results indicated a significant correlation between food choice practices and the consumption of foods that worsen nutritional status (Carbohydrates and street food). The structures that played a role as barriers or enablers of the social practices of food choice included control over income, control over means of transportation, control over the selection of various types of food supplied from outside the community, food regulations for children who suffer from pain, family support and parenting norms. Conclusion: These results suggested that to overcome malnutrition issues, policies for nutritional improvement should consider relevant social structures.